Analisis Getaran pada Generator Magnet Permanen 1kW Hasil Rancang Bangun Pusat Penelitian Tenaga Listrik dan Mekatronik - Pudji Irasari; Aditya Sukma Nugraha; Muhammad Kasim (Journal of Mechatronics, Electrical Power and Vehicular Technology, 2010)
Vibration in a generator is an important factor in detail of design. To know the behavior of the vibration, a test is performed using vibratiometer. The aim in writing this paper is to obtain reference classification of vibration that can be viewed on a standard IEC 34-14 and DIN EN 60034-14. In this paper the results of testing, the value of velocity and acceleration, will be measured analytically so asto create value that can be used to compare the value of the test results with the value from 34-14 IEC and DIN EN 60034-14 standards.